Pengaruh Penambahan Probiotik EM-4 (Evective Mikroorganism-4) Dalam Pakan Terhadap Pertumbuhan Dan Kelangsungan Hidup Ikan Gurame (Osprhronemus gouramy) - Sri Yuningsih Noor; Rano Pakaya (Gorontalo Fisheries Journal, 2018)
The purpose of this study was to determine the effect of the addition of probiotic EM4 (Evective Microorganism-4) in feed to growth and gouramy ointment (Osprhronemus gouramy) at the Freshwater Fish Seed Development Center in Gorontalo Province. The method of this research is experimental method and data processing using completely Randomized Design with 4 treatments 3 replicates. The treatment is done with different doses which in treatment A (Without Probiotic), B ( probiotic 1 cc), C (probiotic 2 cc), D (probiotic 3 cc). The parameters observed were growth rate, Feed Conversion (KP). Feed Efficiency (EP), and Absolute Length (PM). The data were tested continued using the LSD test (Least Significance Different). The results showed that the effect of giving EM4 probiotic with different dose to the growth rate of gouramy fish (Osprhronemus gouramy) gave a very real effect, and from the four research results it was found that treatment D with 3 cc dose was the highest value, followed by C 2 treatment cc, treatment B with a dose of 1 cc and the lowest is in treatment A (Control). Keywords : Probiotic EM-4, gouramy (Osprhronemus gouramy), Growth.